(untitled) (Fiep Bulletin - online, 2016)
The aim of this study was to evaluate the functional autonomy of 15 individuals aged 60 (sixty) and 69 (sixty nine) years, attending the popular Academy of Murici through a battery of tests developed by the Latino Development Group -American to Maturity (GDLAM). The tests consist of walking 10 meters (C10m), getting up from a seated position (LPS), getting up from the prone position (LPDV) and get up from the chair and walk around the house (LCLC). In which the elderly themselves available to participate in the test by signing a consent form, done that was marked the day for the realization of the same in Murici-AL municipal People’s Academy. Implemented four tests, the elderly repeated twice for each test, thereby computing the best result in each of them. It was concluded therefore that the tests used to assess the functional autonomy to carry out the activities of daily living ADL are important and reliable tools to measure the degree of functional autonomy of the elderly.